Strategi Dinas Parawisata Provinsi Maluku Dalam Meningkatkan Kunjungan Wisata - Atamimi, Fitriavni; Madubun, Jusuf; Khairunnisa, Atikah (Journal of Government Science Studies, 2024)
This research is a qualitative research that aims to analyze the strategy of the Tourism Office in increasing tourist visits (Case study on World Peace Gong). This research was conducted at the Maluku Province Tourism Office. Data collection is obtained through primary data and secondary data. The results showed that the GPD historical tourist destination is one of the tourist attractions managed directly by the Maluku Province Tourism Office. In its management, there are obstacles, namely the lack of parking lots, some infrastructure that is starting to be damaged, the lack of quality of tourism human resources and the lack of promotion carried out by the Maluku Province Tourism Office. It is expected from this research that the Tourism Office can improve the quality of tourism human resources, can develop the capacity of tourism businesses and the creative economy, can develop tourism facilities and infrastructure as a support in developing tourism potential and can optimize technology in promoting GPD to be widely known by the public, thus increasing tourist visits.